Mixed convection boundary layer flow about a solid sphere with convective boundary conditions - Mohd Zuki, Salleh; Alkasasbeh, Hamzeh Taha; Razman, Mat Tahar; Roslinda, Nazar; Pop, Loan (Landesmuseum Kärnten, 2014)
In this paper, the steady mixed convection boundary layer flow on a solid sphere with convective boundary conditions, in which the heat is supplied through a bounding surface of finite thickness and finite heat capacity, is considered. The boundary layer equations are transformed into non-dimensional form and are reduced to a nonlinear systemof partial differential equations, which are solved numerically using an implicit finite-difference scheme known as the Keller-box method. Numerical solutions are obtained for the local skin friction coefficient, the local heat transfer coefficient, as well as the velocity and temperature profiles. The features of the flow and heat transfer characteristics for different values of the mixed convection parameter, the Prandtl number Pr, the conjugate parameter and the coordinate running along the surface of the sphere, x, are analyzed and discussed